Review on concepts of wound healing - Swetha; C., Kiran kumar; P, Venkatesh (International Journal of Indigenous Herbs and Drugs, 2022)
Understanding wound healing at multiple levels – biochemical, physiologic, cellular and molecular provides the surgeon with basic clinical decisions. This review article describes the classification of wounds, wound healing, phases of wound, factors, wound dressing.